High-performance liquid chromatographic and subcritical fluid chromatographic separation of alpha-arylated ss-carboline, N-alkylated tetrahydroisoquinolines and their bioisosteres on polysaccharide-based chiral stationary phases - Bajtai Attila (JOURNAL OF SEPARATION SCIENCE, 2019)
New, pharmacologically interesting chiral amino compounds, namely, stereoisomers of alpha-hydroxynaphthyl-ss-carboline, benz[d]azepine and benz[c]azepine analogs as well as N-alpha-hydroxynaphthylbenzyl-substituted isoquinolines were enantioseparated by high-performance liquid chromatographic and subcritical fluid chromatographic methods on polysaccharide-based chiral stationary phases. Separation of the stereoisomers was optimized in both subcritical fluid chromatography and normal phase liquid chromatographic modes by investigating the effects of the composition of the bulk solvent, temperature, and the structures of the analytes and selectors. Both normal phase liquid chromatography and subcritical fluid chromatography exhibited satisfactory performance, albeit with somewhat different effectiveness in the separation of the stereoisomers studied. The optimized methods offer the possibility to apply preparative-scale separations thereby enabling further pharmacological investigations of the enantiomers.